2004
DOI: 10.1212/01.wnl.0000144343.91136.cf
|View full text |Cite
|
Sign up to set email alerts
|

Severe cardiac arrhythmias in young patients with myotonic dystrophy type 1

Abstract: Cardiac tachyarrhythmias have rarely been studied in young patients with myotonic dystrophy type 1 (DM1). The authors observed major cardiac rhythm disturbances in 11 patients aged 10 to 18 years. Tachyarrhythmic events were more frequent than impulse conduction disorders. Wide variations in CTG expansion were observed among the population. Since physical exercise was a prominent arrhythmogenic factor, systematic exercise tests with EKG monitoring may be indicated in young patients with DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 6 publications
1
62
0
7
Order By: Relevance
“…79,88,89,206,207 Rarely, dilated cardiomyopathy and HF can occur. 208 Thus, patients with DM and their care providers should be questioned as to the presence of syncope, palpitations, or breathlessness, 79,209 and electrocardiographic abnormalities, non-sinus rhythm, prolongation of the QRS interval (particularly with evidence of HV-interval prolongation), PR interval >240 ms, or higher degree of atrioventricular block should be regarded as a risk factor for sudden death.…”
Section: Cardiac Evaluation In Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…79,88,89,206,207 Rarely, dilated cardiomyopathy and HF can occur. 208 Thus, patients with DM and their care providers should be questioned as to the presence of syncope, palpitations, or breathlessness, 79,209 and electrocardiographic abnormalities, non-sinus rhythm, prolongation of the QRS interval (particularly with evidence of HV-interval prolongation), PR interval >240 ms, or higher degree of atrioventricular block should be regarded as a risk factor for sudden death.…”
Section: Cardiac Evaluation In Dmmentioning
confidence: 99%
“…79,210,211 Because physical exertion has been observed to be a proarrhythmic influence, serial exercise stress testing has been recommended for young DM1 patients. 207 CMR can be requested to noninvasively assess fatty infiltration and fibrosis in the myocardium. 212,213 An electrophysiology study may be indicated in anticipation of pacemaker/ICD implantation …”
Section: Cardiac Evaluation In Dmmentioning
confidence: 99%
“…Conduction defects have been evidenced in Duchenne muscular dystrophy [41,42], Becker muscular dystrophy [43,44], myotonic dystrophy type 1 and 2 [45,46], Emery-Dreifuss muscular dystrophy [47], and limb girdle muscular dystrophy [48,49].…”
Section: Pkcs and Muscular Dystrophiesmentioning
confidence: 99%
“…Cardiac abnormalities can be diagnosed as early as the second decade of life in the childhood type (79). Conduction disturbances occur in 65% of adults (80); pathology studies showed fibrosis of conduction system and diffuse interstitial fibrosis throughout the myocardium (81).…”
Section: Cardiac Disease In Dm1mentioning
confidence: 99%